Analisis Hashtag pada Twitter untuk Eksplorasi Pokok Bahasan Terkini Mengenai Business Intelligence - Arif Himawan; Muhammad Rifqi Maarif; Ulfi Saidata Aesyi (JISKA (Jurnal Informatika Sunan Kalijaga), 2021)
The main purpose of this paper is to examine the dominant topics about Business Intelligence in micro-blogging Twitter. There are 7.153 tweets collected from Twitter API. Text mining and natural language processing are used to analyze the dominant topics among those tweets. Computational method used to count the most frequent hashtag that appears together with Business Intelligence hashtag. Twitter users are large and scattered around the world with a diverse range of skills (expertise) that can give a new perspective on a subject that may not be predicted before. For example, for topics related to Business Intelligence, the very dominant general topic discussed in the scientific literature are about data management, as well as for analytics and machine learning data. The result contributes to understanding dominant topics about Business Intelligence that can help researchers to level their research.